Saksi Wanita dalam Putusan Perceraian di Pengadilan Agama Kelas IA Kota Jambi - Jantan Saparuddin; Maryani Maryani (INNOVATIO: Journal for Religious Innovation Studies, 2016)
In examining and resolving marital disputes in divorce cases special procedural law is regulated, which is regulated in Law Number 1 of 1974 concerning marriage, Government Regulation Number 9 of 1975 concerning the implementation of Law Number 1 of 1974, Law Number 7 Year 1989 concerning the Religious Courts and Compilation of Islamic Law. Among the duties of judges in resolving divorce cases is to worry or judge whether the events or facts presented by the parties are true and this can only be done through verification. This study aims: first, to know the role and position of female witnesses for divorce cases in the Jambi City Religious Court according to Islamic law; second, knowing the role and position of female witnesses for divorce cases in the Jambi City Religious Courts according to Indonesian law. Second, knowing the role and position of female witnesses for divorce cases in the Jambi City Religious Courts according to the laws in Indonesia. The research method used is an empirical juridical method, which is used to analyze various laws and regulations in the field of marital law. While the empirical approach is used to analyze the law not merely as a set of normative legislation, but the law is seen as the behavior of people who fluctuate and pattern in people's lives. The approach method used in this study is an empirical juridical method, which is used to analyze various laws and regulations in the field of marital law. While the empirical approach is used to analyze the law not merely as a set of normative legislation, but the law is seen as the behavior of people who fluctuate and pattern in people's lives.